Cognitive Impairment Precedes and Predicts Functional Impairment in Mild Alzheimer’s Disease - Hong Liu‐Seifert; Eric Siemers; Karen Price; Baoguang Han; Katherine J. Selzler; David Henley; Karen Sundell; Paul Aisen; Jeffrey L. Cummings; Joel Raskin; Richard C. Mohs (2015)
Background: The temporal relationship of cognitive deficit and functional impairment in Alzheimer's disease (AD) is not well characterized.Recent analyses suggest cognitive decline predicts subsequent functional decline throughout AD progression.Objective: To better understand the relationship between cognitive and functional decline in mild AD using autoregressive cross-lagged (ARCL) panel analyses in several clinical trials.Methods: Data included placebo patients with mild AD pooled from two multicenter, double-blind, Phase 3 solanezumab (EXPEDITION/2) or semagacestat (IDENTITY/2) studies, and from AD patients participating in the Alzheimer's Disease Neuroimaging Initiative (ADNI).Cognitive and functional outcomes were assessed using AD Assessment Scale-Cognitive subscale (ADAS-Cog), AD Cooperative Study-Activities of Daily Living instrumental subscale (ADCS-iADL), or Functional Activities Questionnaire (FAQ), respectively.ARCL panel analyses evaluated relationships between cognitive and functional impairment over time.Results: In EXPEDITION, ARCL panel analyses demonstrated cognitive scores significantly predicted future functional impairment at 5 of 6 time points, while functional scores predicted subsequent cognitive scores in only 1 of 6 time points.Data from IDENTITY and ADNI programs yielded consistent results whereby cognition predicted subsequent function, but not vice-versa.Conclusions: Analyses from three databases indicated cognitive decline precedes and predicts subsequent functional decline in mild AD dementia, consistent with previously proposed hypotheses, and corroborate recent publications using similar methodologies.Cognitive impairment may be used as a predictor of future functional impairment in mild AD dementia and can be considered a critical target for prevention strategies to limit future functional decline in the dementia process.